INFLUENCE OF ZAROASTRIANISM ON RELIGION AND PHILOSOPHY - Nilufar Khalimova; Abdullayeva Yodgora Qilichbek qizi (Western European Studies, 2025)
This article covers the origins , history of Zoroastrianism , the duties of its goddesses , the creation of the Zoroastrian book, The "Avesto", and the commentary on the rules of the law set out in it, as well as some legends in Zoroastrianism. It is in this article that some of the sentences presented in the book" avesto " describe how well they fit or do not fit into modern life , as well as some errors.
Keywords: Zaroastrianism; Avesto”; Ahura Mazda